ASEAN Manufacturing Resilience: Financial Lessons from Geopolitical Crises - Rusliansyah Rusliansyah; Muhammad Ramadhani Kesuma (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Geopolitical disruptions fundamentally challenge the financial stability of manufacturing firms in emerging economies, particularly those deeply embedded in global supply chains. This study examines how liquidity coverage ratio (LCR), debt-to-equity ratio (DER), total asset turnover ratio (TATO), and firm size (FS) influence the financial resilience of ASEAN manufacturing firms, measured by current ratio (CR) and net income (NI). Using a balanced panel of 391 publicly listed firms across Indonesia, Malaysia, the Philippines, Thailand, and Singapore over 2020-2024, a period marked by acute geopolitical volatility, we employ fixed-effects (FE) and random-effects (RE) panel regression as determined by the Hausman test. Our results reveal that LCR significantly enhances both CR and NI, affirming liquidity as the primary driver of resilience. DER positively affects CR but not NI, suggesting strategic short-term debt use bolsters short-term liquidity in emerging market contexts without proportionate profitability gains. TATO exerts no significant effect on either outcome, consistent with the view that asset efficiency loses relevance during operational disruptions. FS significantly enhances NI but not CR, highlighting scale advantages in sustaining profitability. These findings offer three contributions: they extend liquidity theory to ASEAN's export-driven context; challenge conventional capital structure assumptions in emerging markets; and provide a historical evidence base for managing the recent Iran-Israel conflict's disruptions. Practical implications are drawn for firm-level cash flow management and for policymakers designing credit support and regional trade integration frameworks.